Peranan Media Audio Visual dalam Meningkatkan Prestasi Belajar Sejarah Siswa Kelas XI MA NU Asy’ariyyah Pati - Rusita Fitriana Wihartatik; Nabila Syafa Ardana; Rofiq Faudy Akbar (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2024)
A learning process that takes place in an expository and conventional manner will make students passive and less likely to master the material presented because the class atmosphere is boring. With that, we need learning media to help achieve learning goals. The aim of this research is to improve student achievement by utilizing audio-visual learning media. The subjects of this research were class XI B students at MA NU Asy'ariyyah Pati. This research uses the type of research, namely PTK or Classroom Action Research and direct observation as data collection techniques. This research cycle consists of 4 stages which include; The Planning Stage, the Acting Stage, the Observing Stage and finally the Reflection Stage. The results of the research show that the use of Audio Visual Learning Media in the History subject, the theme of the Proclamation of Independence, material on the Defeat of Japan, Towards the Proclamation of Independence and the Moments of the Proclamation for class XI B MA NU Asy'ariyyah Pati has proven to be effective in improving the results of students' history learning, so it can be an alternative problem solving to overcome the problem of passivity and low student learning achievement. The increase in learning achievement, namely the KKM score before Classroom Action Research, was 33%, and there was an increase to 100%. The lowest score achieved by students in this cycle is 70 and the highest is 100